Liana infestation impacts tree growth in a lowland tropical moist forest - G. M. F. van der Heijden (Biogeosciences, 2009)
Ecosystem-level estimates of the effect of lianas on tree growth in mature tropical forests are needed to evaluate the functional impact of lianas and their potential to affect the ability of tropical forests to sequester carbon, but these are currently lacking. Using data collected on tree growth rates, local growing conditions and liana competition in five permanent sampling plots in Amazonian Peru, we present the first ecosystem-level estimates of the effect of lianas on above-ground productivity of trees. By first constructing a multi-level linear mixed effect model to predict individual-tree diameter growth model using individual-tree growth conditions, we were able to then estimate stand-level above-ground biomass (AGB) increment in the absence of lianas. We show that lianas, mainly by competing above-ground with trees, reduce tree annual above-ground stand-level biomass increment by ~10%, equivalent to 0.51 Mg dry weight ha−1 yr−1 or 0.25 Mg C ha−1 yr−1. AGB increment of lianas themselves was estimated to be 0.15 Mg dry weight ha−1 yr−1 or 0.07 Mg C ha−1 yr−1, thus only compensating ~29% of the liana-induced reduction in ecosystem AGB increment. Increasing liana pressure on tropical forests will therefore not only tend to reduce their carbon storage capacity, by indirectly promoting tree species with low-density wood, but also their rate of carbon uptake, with potential consequences for the rate of increase in atmospheric carbon dioxide.